Corporate governance and firm performance in developing countries: evidence from India. Issue 2 (4th April 2016) - Arora, Akshita; Sharma, Chandan
Abstract : Purpose: This study aims to examine the impact of corporate governance on firm performance for a large representative sample. Design/methodology/approach: This empirical analysis focuses on a large number of companies covering 20 important industries of the Indian manufacturing sector for the period 2001-2010. Several alternative specifications and estimation techniques are used for analysis purposes, including system generalized methods of moments, which effectively overcomes the problem of endogeneity and simultaneity bias. Findings: On one side, the findings indicate that larger boards are associated with a greater depth of intellectual knowledge, which in turn helps in improving decision-making and enhancing the performance. On the other side, the results indicate that return on equity and profitability is not related to corporate governance indicators. The results also suggest that CEO duality is not related to any firm performance measures for the sample firms. Practical implications: The outcomes of the analyses advocated that companies that comply with good corporate governance practices can expect to achieve higher accounting and market performance. It implies that good corporate governance practices lead to reduced agency costs. Hence, it is concluded that firms of the developing world can possibly enhance their performance by implementing good corporate governance practices. Originality/value: Departing from the conventional system of the prior studies and instead of focusing on a single measure framework, a range of measures of corporate governance and firm's performance variables are used. Also, several alternative specifications and estimation techniques are used for analysis purposes. Furthermore, the sample also covers a large sample of manufacturing firms.